JUKWAA LA TAARAB - ZANZIBAR, by Issa Mgana, Mediafrica Books, Helsinki 1991, 10lpp, photos, charts, song texts, KiSwahili text. - Topp Fargion, Janet (International Library of African Music, 1996)
pages: 125-129
Keywords: African Music